2003
DOI: 10.1097/00005176-200307000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Celiac Disease and Follow-up of EMA in Children and Adolescents With Type 1 Diabetes Mellitus

Abstract: This study emphasizes the high prevalence of CD in patients with DM. Although several patients already had positive EMA titers at the onset of DM, seroconversion may also occur during the course of the disease. Screening for CD with EMA or tissue transglutaminase should be included in the initial investigation of DM, but should also be repeated over time to detect late seroconversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0
13

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 16 publications
5
49
0
13
Order By: Relevance
“…After review of abstracts and full texts, 596 studies were excluded (Fig 1), leaving 9 cohort studies that met the inclusion criteria. 1,7,8,17,[24][25][26][27][28] The studies were from Europe (n = 7) and Australia (n = 2). Study characteristics are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…After review of abstracts and full texts, 596 studies were excluded (Fig 1), leaving 9 cohort studies that met the inclusion criteria. 1,7,8,17,[24][25][26][27][28] The studies were from Europe (n = 7) and Australia (n = 2). Study characteristics are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Despite many similarities between DM1 and CD, such as underlying genetic susceptibility associated with HLA class II and autoimmune phenomena, the prevalence rate of CD in DM1 appears to differ greatly in different geographical areas (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Both diseases were associated with a high frequency of HLA DQA1* 0501 and DQB1*0201 (DQ2) molecules worldwide (5).…”
Section: Discussionmentioning
confidence: 99%
“…23 The previous literature reported contradictory results between the sexes for the prevalence of CD in T1DM. The prevalence was higher in females in some studies, 13,24 higher in males in others, 25,26 and yet other studies reported no difference. 27,28 However, a meta-analysis published in 2014 described no sex predominance in the prevalence of CD in T1DM.…”
Section: Epidemiologymentioning
confidence: 79%